2009
DOI: 10.1186/1471-2202-10-47
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal and anterior cingulate cortex abnormalities in Tourette Syndrome: evidence from voxel-based morphometry and magnetization transfer imaging

Abstract: Background: Pathophysiological evidence suggests an involvement of fronto-striatal circuits in Tourette syndrome (TS). To identify TS related abnormalities in gray and white matter we used optimized voxel-based morphometry (VBM) and magnetization transfer imaging (MTI) which are more sensitive to tissue alterations than conventional MRI and provide a quantitative measure of macrostructural integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
103
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 50 publications
18
103
0
3
Order By: Relevance
“…MRI analyses have detected volumetric changes in the cortex of TS patients including larger dorsal prefrontal and parieto-occipital regions, and a smaller inferior occipital region (Peterson et al, 2001). In a limited but well controlled male-only study that excluded medicated patients and those with comorbidities, voxel-based morphometry and magnetization transfer imaging (methods sensitive to tissue alterations and macrostructural integrity) have detected changes in prefrontal, frontal, sensorimotor, and anterior cingulate regions (Müller-Vahl et al, 2009). Using parcellation methods, variable changes have been reported in subcortical white matter, with increases in the right frontal region (Fredericksen et al, 2002) or decreases in left deep frontal white matter .…”
Section: Cortex and Subcortical White Mattermentioning
confidence: 99%
“…MRI analyses have detected volumetric changes in the cortex of TS patients including larger dorsal prefrontal and parieto-occipital regions, and a smaller inferior occipital region (Peterson et al, 2001). In a limited but well controlled male-only study that excluded medicated patients and those with comorbidities, voxel-based morphometry and magnetization transfer imaging (methods sensitive to tissue alterations and macrostructural integrity) have detected changes in prefrontal, frontal, sensorimotor, and anterior cingulate regions (Müller-Vahl et al, 2009). Using parcellation methods, variable changes have been reported in subcortical white matter, with increases in the right frontal region (Fredericksen et al, 2002) or decreases in left deep frontal white matter .…”
Section: Cortex and Subcortical White Mattermentioning
confidence: 99%
“…27 Another morphometric study has demonstrated that white matter was significantly increased in the right ventroposterolateral part of the thalamus in patients with Tourette's syndrome compared with healthy age-and sex-matched controls. 28 Furthermore, it has also been reported that DBS of the right nucleus accumbens was associated with an improvement in tics.…”
Section: Unilateral Gpi Dbs In Tsmentioning
confidence: 99%
“…Among these individuals, there seems to be a failure of the cerebral plasticity mechanism that allows compensation for the presence of tics by overactivation of a motor inhibition process. Unlike adults, children with GTS have a larger orbitofrontal volume [32] and bilateral putamen [33,34], which would constitute an adaptive plasticity in response to the expression of tics, which, in turn, would help to inhibit them more easily. With the maturation of the prefrontal cortex during adolescence, this mechanism could gain strength and explain the symptom decrease during adolescence and early adulthood.…”
Section: ▪ Etiologies Of Gts: a 3d Modelmentioning
confidence: 99%